Socio-economic consequences of retired people in Peninsular Malaysia / Normah Mohd. Dali, Appa Rao Maradiah and Lau Too Kya - Mohd. Dali, Normah; Appa Rao, Maradiah; Lau, Too Kya (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
This study on Socio-Economic Consequences of Retired People on Malaysia attempts to identify the current life-style of the retirees. It addresses the socio-economic and psychological aspects of Malaysian retirees and highlights the possibility of utilisation of their skills for the economic development of the country. Both the qualitative and quantitative modes of research were resorted to. A comprehensive structured questionnaire was used in the face-to-face interview with the selected retirees in Peninsular Malaysia. Records from the Employees' Provident Fund and the Pension Department were used as the sampling frame. One thousand and eleven respondents were interviewed from Johore, Selangor, Kuala Lumpur, Kedah and Terengganu. The majority of the Malaysian retirees led a simple and healthy life-style tending to daily activities such as watching movies, listening to radio programmes, looking after grandchildren and participating in social activities.